Modified dindo-clavien system for registration of perioperative complications in children undergoing adenotonsillectomy - Arens, Philipp; Hardt, Juliane; Angrick, Julie Charlotte; Olze, Heidi; Coordes, Annekatrin (Frontiers in Pediatrics, 2022)
Introduction: Surgical procedures in children are among the most commonly performed procedures in otolaryngology. Perioperative safety and documentation of complications are becoming increasingly important. This study investigates perioperative complications in a clinical cohort of children with adenotonsillar hyperplasia undergoing adenotonsillectomy using the standardized Dindo-Clavien reporting system. Patients and Methods: Retrospective evaluation of 402 children who underwent adenotonsillectomy between 2009 and 2015. Patient parameters including all perioperative complications were investigated. Results: In the study, 124 complications were found (106 mild, 16 severe). According to the Dindo-Clavien classification, 93 grade I, 15 grade II, 5 grade III, 11 grade IV and 0 grade V complications were documented. Complications were associated with additional diagnoses (p=0.001), long-term medication intake (p=0.003), duration of hospitalization (p<0.001) and duration of surgery (p<0.001), undergoing tonsillotomy (p=0.022) or tonsillectomy (p<0.001), differences in ASA score (p=0.005) and differences in OSA-18 score (p=0.011). Severe complications, classified as grade III and IV, were associated with premature birth (p=0.026), additional diagnoses (p=0.017), long-term medication intake (p<0.001) and differences in ASA score (p=<0,001). Conclusion: The Dindo-Clavien classification is a standardized reporting system which can also be used for surgical procedures in children with adenotonsillar hyperplasia. The system shows associations with clinical parameters and thus can help to identify subgroups at risk of severe complications.